Nutritional importance of animal-sourced foods in a healthy diet - Sheffield, Sydney; Fiorotto, Marta L.; Davis, Teresa A. (Frontiers in Nutrition, 2024)
Animal-sourced foods, such as meats, poultry, eggs, milk, and fish are nutrient-dense foods that are rich sources of protein, essential amino acids, and micronutrients that can be challenging to obtain solely through plant-based foods. Animal-sourced protein foods provide crucial nutrients that support the growth and development in children, maintenance of muscle mass and function in adults, gain in muscle mass and strength in exercising individuals, and mitigation of sarcopenia in the elderly. The 2020-2025 Dietary Guidelines for Americans have identified the important role of animal-sourced foods in the diet at every stage of life. Animal-sourced foods are consumed worldwide and contribute to global food security.